The Impact of Market-related Factors on the Choice of Foreign Market Entry Mode by Service Firms - Šarapovas, Tadas; Huettinger, Maik; Ričkus, Domas (Organizations and Markets in Emerging Economies, 2016)
The topic of internationalization has received an increased amount of attention due to globalization and growing amounts of international trade. One of the most important factors for the success of foreign market operations is the choice of the entry mode. This paper investigates the key determinants for the choice of foreign market entry mode. Specifically, the research examines the effects of market-related factors of the selected entry mode on service companies. This study contributes to the existing knowledge of internationalization of service companies by analyzing market-related factors of entry modes. Moreover, it provides managerial implications that might be applied by companies and governmental agencies to promote investment and internationalization of local companies.